MATERIALS AND (LANGUAGE) LEARNING ENVIRONMENT BASED ON MONTESSORI CONCEPTS - Christina Kristiyani (LLT Journal: A Journal on Language and Language Teaching, 2018)
Montessori Education is widely spread in almost all countries in the world. Even though this school is meant for all kinds of learners including normal learners, the Montessori education concepts used in Montessori schools will be very supportive education for children with special needs. Therefore, the schools which adopt Montessori education concepts can facilitate inclusion, especially with the concepts of I can do it myself. Inclusive education needs to be carefully prepared and implemented by schools. The movement brings about some challenges for teachers. This paper explores the environment and materials based on Montessori education concepts. The environment and materials are suitable for all types of learners and thus can be an option to be implemented in the inclusive education setting. Teaching materials rooted in Montessori education concepts indeed cater all ages and embrace the needs of all students.